Allergic contact dermatitis in patients with chronic leg ulcers - Czarnecka-Operacz, Magdalena; Żmudzińska, Maria (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Contact allergy co-existing with leg ulcers creates difficult clinical problem from both diagnostic and therapeutic standpoint. It affects up to 60–70% patients with leg ulcers and hypersensitivity to glucocorticosteroids is found in 2.6–5% of cases. Recently the increased number of positive patch tests results, including corticosteroids has been observed. Tixocortol pivalate and budesonid are recognized as screening markers and combination of both of them enables to identify more then 90% of glucocorticosteroid contact allergy. It is considered that the degree of chronic venous insufficiency may influence not only the clinical picture of leg ulcers but also the co-existing contact dermatitis, which also becomes the complicating factor of ulcer healing process.